Implementasi Algoritma Regresi Linier untuk Mengukur Tingkat Pengeluaran Co2 Pada Kendaraan Bermotor - Kevin Asgaryansyah; Paniran Paniran (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study employs a linear regression algorithm to measure CO2 emissions from motor vehicles based on the type of fuel used—gasoline, premium, diesel, and ethanol—as well as the distance traveled per kilometer. With growing concerns about the environmental impact of vehicle emissions, this research aims to develop a predictive model to estimate CO2 emissions based on these variables. Despite the limited data used, the results indicate that the linear regression model has high accuracy in predicting CO2 emissions. This model can serve as an effective tool to mitigate the environmental impact of motor vehicles and assist policymakers in designing better emission mitigation strategies